Drug-Loaded Photosensitizer-Chitosan Nanoparticles for Combinatorial Chemo- and Photodynamic-Therapy of Cancer - Pandya, Abhilash D; Øverbye, Anders; Sahariah, Priyanka; Gaware, Vivek S; Høgset, Håkon; Masson, Màr; Høgset, Anders; Mælandsmo, Gunhild M; Skotland, Tore; Sandvig, Kirsten; Iversen, Tore-Geir (Biomacromolecules, 2020)
In this study we have developed biodegradable polymeric nanoparticles (NPs) containing the cytostatic drugs mertansine (MRT) or cabazitaxel (CBZ). The NPs are based on chitosan (CS) conjugate polymers synthesized with different amounts of the photosensitizer tetraphenylchlorin (TPC). These TPC–CS NPs have high loading capacity and strong drug retention due to π–π stacking interactions between the drugs and the aromatic photosensitizer groups of the polymers. CS polymers with 10% of the side chains containing TPC were found to be optimal in terms of drug loading capacity and NP stability. The TPC–CS NPs loaded with MRT or CBZ displayed higher cytotoxicity than the free form of these drugs in the breast cancer cell lines MDA-MB-231 and MDA-MB-468. Furthermore, light-induced photochemical activation of the NPs elicited a strong photodynamic therapy effect on these breast cancer cells. Biodistribution studies in mice showed that most of the TPC–CS NPs accumulated in liver and lungs, but they were also found to be localized in tumors derived from HCT-116 cells. These data suggest that the drug-loaded TPC–CS NPs have a potential in combinatory anticancer therapy and as contrast agents.